The 80/20 manager : ten ways to become a great leader - Koch, Richard, 1950- (New York : Little, Brown, 2013)
In his bestselling book The 80/20 Principle, Richard Koch showed readers how to put the 80/20 Principle--the idea that 80 percent of results come from just 20 percent of effort--into practice in their personal lives. Now in THE 80/20 MANAGER, he demonstrates how to apply the principle to management. An 80/20 manager learns to focus only on the issues that really matter, achieving exceptional results, and feeling successful everyday while working less hard in fewer hours. A large number of managers--especially in these difficult times--feel completely overwhelmed. Their inboxes are overflowing and they constantly struggle to finish their to-do lists, leaving little time for the things that really matter. THE 80/20 MANAGER shows a new way to look at management--and at life--to enjoy work and build a successful and fulfilling career.
Would you like to simplify your work and life? -- The secret weapon -- The investigating manager -- The superconnecting manager -- The mentoring manager -- The leveraged manager -- The liberating manager -- The manager seeking manager -- The time-rich manager -- The simplifying manager -- The lazy manager -- The strategic manager.
Includes bibliographical references (p. 251-257) and index.
Keywords: Executive ability; Management; Time management; Success in business